Mapping of Malay architectural heritage in Gombak district, Selangor - Salleh, Nurul Hamiruddin; Abdullah, Mohammad Zaim; Ab Jalil, Nurlelawati; Shaharil, Muhammad Ihsan (IIUM Press, 2022)
Gombak District in the Klang valley contributes considerable importance to the history of Malay settlement which traces back hundreds of years that led to the existence of Malay architectural heritage in the Gombak district. Hence, this research seeks to inventory the current condition of Malay architectural heritage in Gombak. The research methodology involved a literature review, onsite inventory, and face-to-face semi-structured interviews. Thirty-two (32) Malay traditional houses and masjids from 21 villages in Gombak have been inventoried. Most of them were built for over 80 years, while a few were 140 years old. The research also revealed that ten (10) heritage buildings are still in good condition and reasonably preserved. Proactive preservation initiatives and conservation efforts must be carried out continuously to conserve the traditional Malay houses and masjids to be appreciated by future generations.